The Correlation Between Spiritual Intelligence And Emotional Intelligence With Self Care Management In Type 2 Diabetes Mellitus (DM) Patients In The Orchid Room RSD dr. Haryoto Lumajang - Nurakhmawati, Eva; Marfuah, Marfuah; Aini Isnawati, Iin (NHM PRESS, 2023)
Diabetes Mellitus (DM) is a chronic disease because the pancreas is no longer able to produce insulin. People with DM must have good spiritual and emotional intelligence in order to self care management in people with DM so that complications can be controlled or not occur. This study aims to determine the correlation between Spiritual Intelligence and Emotional Intelligence with Self Care Management in Patients with Type 2 Diabetes Mellitus in the Orchid Room, RSD dr. Haryoto Lumajang. This type of research is correlational analytic cross sectional approach. Population was 32 people, 30 samples determined using technique Accidental sampling. The instruments used Spiritual Intelligence, Emotional Intelligence and Questionnaires Self Care Management. Data processing with Editing, Coding, Scoring and Tabulating processes, then analyzed using Logistic Regression. The results of this study indicate respondents have a low category of spiritual intelligence with a total of 12 people (40%), respondents have a low category of emotional intelligence with a total of 11 people (36.7%), and respondents have Self Care Management less category with a total of 14 people (47%). The results of the analysis test using Logistic Regression have a correlation between Spiritual Intelligence and Emotional Intelligence with Self Care Management. in Type 2 DM Patients in the Orchid Room, RSD dr. Haryoto Lumajang with sig value for the effect of X1 and X2 simultaneously on Y is 0.000 <0.05 and the calculated F value is 218,755 > F table 3.32 so it can be concluded that H0 is accepted.